Insider lending banks, personal connections, and economic development in industrial New England - Lamoreaux, Naomi R. 1950- (Cambridge University Press, 1994)
The term insider lending conveys an aura of abuse and corruption, of unethical, if not illegal, behaviour. In early nineteenth-century New England, however, insider lending was an integral aspect of the banking system. Not only was the practice an accepted fact of economic life, but, as Naomi R. Lamoreaux argues, it enabled banks (at least in this particular historical context) to play an important role in financing economic development. As the banking system evolved over the course of the century, however, lending practices became more impersonal and professional. Ironically, the information problems banks faced when they began to conduct more and more of their business at arm's length forced them to concentrate on providing short-term loans to commercial borrowers and to give up financing economic development. This book was first published in 1994
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1800-1900; Geschichte 1830-1914; Bank; Geschichte; Banks and banking / New England / History / 19th century; Commercial loans / New England / History / 19th century; Economic development projects / New England / Finance / History / 19th century; Asset-backed financing / New England / History / 19th century; Kreditgewährung; Kreditwesen; Neuengland